Aerosol pollution alters the diurnal dynamics of sun and shade leaf photosynthesis through different mechanisms. (7th August 2022) - Wang, Zhenhua; Wang, Chengzhang; Wang, Xin; Wang, Bin; Wu, Jin; Liu, Lingli
Abstract: Anthropogenic aerosols have been shown to perturb CO2 exchange between the vegetation and the atmosphere. However, the climate effects of aerosols through carbon cycle feedback still have significant uncertainties. Taking advantage of the periodic fluctuations of aerosol loading in Beijing, we intensively measured the diurnal course of leaf microclimates and photosynthesis under different aerosol conditions during the growing season in 2014 and 2015. We found that increasing aerosol loadings altered the diurnal course of microclimates and thus sun and shade leaf photosynthesis. Our mechanistic photosynthesis model experiments further showed that aerosol‐induced increase in sun leaf photosynthesis occurred around noon and afternoon, mainly by alleviating the depression of photosynthesis caused by high leaf temperature and leaf‐air vapour pressure deficit. Meanwhile, aerosols enhanced shade leaf photosynthesis throughout the day by mitigating the light limitation within the canopy, with the highest increase occurring around noon. Overall, our study suggested that aerosol's diffuse fertilization effect, cooling effect and the accompanying low leaf‐air vapour pressure deficit collectively drove the changes in the diurnal courses of sun and shade leaf photosynthesis. Our results provided an important benchmark for assessing how anthropogenic aerosols regulate ecosystem C balance under different meteorological conditions.